Determining Optimal Strategies for Single-Line Bus Operation by Means of Smartphone Demand Data. Issue 1 (2016) - Tang, Chunyan; Ceder, Avishai (Avi); Zhao, Shengchuan; Ge, Ying-En
Passenger demand along an urban bidirectional bus line is usually neither uniform nor symmetric. In practice, buses are operated along such routes without efficient use of operational routing-related strategies. This work focused on the design of two routing-related strategies, given that fluctuating passenger demand could be estimated with the use of smartphones. In this way, a better match between supply and demand can be attained, and the operational cost involved can be reduced. Optimization formulation was used in this work for the design of routing changes through four possible strategies: full-route operation, short-turn, limited-stop, and a combination of the latter two strategies. The objective function was to minimize the fleet size required to handle the expected demand comfortably by using the onboard loading criterion. This is a practical objective, especially from the operator's perspective. The expected origin–destination demand of a single bus line was constructed on the basis of the existing demand data and potential changes in demand, given service improvement in travel time, waiting time, and seat availability. The potential demand, whether overt or obscure, was assumed to be determinable with the use of smartphone apps, including online service information. A detailed example is used as an expository device for explaining the methodology developed, along with a case study from Dalian, China. The results of the case study show that, by applying the proposed methodology, the fleet size of the single-line bus operation can be reduced by four buses on the basis of the anticipated passenger demand.